Strategies of Working Parents in Fostering Secure Attachment in Early Childhood - Shopia Marwah; Renistiara Medilianasari (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
This study aims to examine the primary strategies employed by working parents to foster secure attachment in young children amidst time constraints. The background of this study is based on the increasing number of working parents, which has the potential to affect the quality of emotional interactions with children during the crucial early developmental period. The study employs a qualitative, descriptive approach to understand parents’ subjective experiences within the context of daily life. The research subjects are working parents with young children, selected through purposive sampling. Data collection was conducted through in-depth interviews, supported by observation  and documentation, and analyzed using thematic analysis. The results indicate that working parents employ parenting strategies focused on the quality of interaction, namely maximizing quality time, establishing consistent daily routines, and maintaining warm, responsive, and open emotional communication. These strategies allow children to continue feeling their parents’ emotional presence despite limited time together. Thus, the formation of secure attachment is not determined by the length of time spent together, but rather by the quality of interactions that are consciously and consistently built by working parents.